1998
DOI: 10.1002/(sici)1096-9128(199809/11)10:11/13<1029::aid-cpe412>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

An infrastructure for network computing with Java applets

Abstract: Java, in combination with Web browsers' abilities to load and execute untrusted Java applets in a secure fashion, has made computing over the Web a possibility. Now the challenge is to fully utilize this potential, given the limitations imposed by browsers. This paper presents KnittingFactory, an infrastructure to facilitate Web‐based computing, which addresses this challenge. It supports building distributed applications, specifically those consisting of Java applets executing in browsers. It is composed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This approach can lead to an even more secure execution environment than a browser itself can provide. For instance, the experiment of the Knitting Factory project [24] found that, when using Java RMI, at least one browser, Sun's HotJava, allowed direct point-to-point communication between applets once RMI handles had been exchanged through the server! Under the old security model, this was not supposed to happen.…”
Section: Java Applets Versus Applicationsmentioning
confidence: 99%
“…This approach can lead to an even more secure execution environment than a browser itself can provide. For instance, the experiment of the Knitting Factory project [24] found that, when using Java RMI, at least one browser, Sun's HotJava, allowed direct point-to-point communication between applets once RMI handles had been exchanged through the server! Under the old security model, this was not supposed to happen.…”
Section: Java Applets Versus Applicationsmentioning
confidence: 99%
“…Besides the portability and interoperability achieved by a standard supporting environment, other features of the language such as its object-oriented programming model, simplicity, robustness, multithreading support, and automatic memory management have proved attractive enough for the development of software projects, especially those intended for large and complex systems. Also, the language portability has been decisive for its choice in projects that consider the use of idle computers, connected to the Internet, to solve large computational problems [5,6,7]. In addition, the growing popularity of the language helps to explain its use in the high-performance computing area.In this survey we describe and classify some Java-based projects aimed directly or indirectly at supporting the development of high-performance networked computing applications.…”
mentioning
confidence: 99%